2022
DOI: 10.1002/aesr.202100208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the High Thermoelectric Performance of Mg3Sb2‐Mg3Bi2 Alloys

Abstract: n‐Type Mg3Sb2‐Mg3Bi2 alloys are some of the most promising thermoelectric materials in the low–mid temperature range. While discovered relatively recently, these materials have garnered intense attention, and numerous papers from the international thermoelectric community have been published in a relatively short period of time. As with all materials, detailed insights into the underlying mechanisms that contribute to these alloys’ distinguished thermoelectric properties are important for future researchers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 100 publications
3
30
0
Order By: Relevance
“…Bi/Sb substitution can not only boost the weighted mobility with reduced effective mass and enhance the low-temperature electrical conductivity with increased grain size but also decrease the lattice thermal conductivity by forming the solid solution. 8 In addition, in this work and the previous reports (see Fig. 1), it can be found that Bi doping leads to an increase in electron concentration.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Bi/Sb substitution can not only boost the weighted mobility with reduced effective mass and enhance the low-temperature electrical conductivity with increased grain size but also decrease the lattice thermal conductivity by forming the solid solution. 8 In addition, in this work and the previous reports (see Fig. 1), it can be found that Bi doping leads to an increase in electron concentration.…”
Section: Introductionsupporting
confidence: 78%
“…5,6 As a typical Zintl phase compound, Mg 3 Sb 2 has an intrinsically low lattice thermal conductivity. 7,8 Since the excellent ntype electrical transport was reported at the end of 2016, 9 the investigation of the thermoelectric properties of n-type Mg 3 Sb 2 has become one of the research hotspots in the field of thermoelectricity. Doping a semiconductor material with donor impurity or acceptor impurity is a common method to increase the concentration of electrons or holes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, doping by Y is more suitable for application than that by Te since the former enables a much better thermal stability upon aging, which might be understood by the higher melting point and lower vapor pressure of Y than those of Te. 45 To study the effect of the sintering temperature, we selected a composition Mg 3.6 Y 0.003 Sb 0.6 Bi 1.4 and sintered it at 973 K, 1023 K, and 1073 K, respectively. Their thermoelectric The obtained maximum conversion efficiency (Z max ), the cooling temperature (DT max ), and the relative output power are compared to other published results.…”
Section: Papermentioning
confidence: 99%
“…As shown in Figure 1a, Mg 3 Bi 2 has a trigonal crystal structure (space group P3m1) with the lattice constants a ¼ b ¼ 4.702 Å and c ¼ 7.436 Å. [20][21][22][23][24][25][26][27][28] The centrosymmetric unit cell contains five alternating Mg and Bi layers stacking along the [001] direction. The bulk Brillouin zone and the projection on (001) surface with high-symmetry points are plotted in Figure 1b.…”
Section: Surface Terminations Of Mg 3 Bimentioning
confidence: 99%